Nexus Between Health Determinants and Health Outcomes: A comparative global analysis - Dillip Kumar Muduli; Pradipta Sahoo; Aiswarya Das; Debasis Pahi (Asia Pacific Journal of Health Management)
The present study examines the nexus between healthcare determinants and health outcomes of different income group countries. For this, the study uses the Feasible Generalized Least Square (FGLS) model on a panel of 143 countries spanning from 2000 to 2019. The findings suggest that total health expenditure and GDP per capita significantly improve health outcomes by reducing infant mortality and increasing life expectancy in all income groups and in all geographic regions. Further, socioeconomic determinants like urbanisation and sanitation significantly contribute in the improvement of health status. Therefore, our results suggest that government health expenditures have to increase to enhance the health outcomes of different countries. At the same time, the policymakers have to focus to increase the income level of the people in order to enhance the health outcomes of the countries.